ACTN3 R577X genotype and performance of elite middle-long distance swimmers in China - Li, Y.; Wang, L. Q.; Yi, L.; Liu, J.; Hu, Y.; Lu, Y.; Wang, M. (Biology of Sport, 2017)
The ACTN3 gene is one of the genes that have a potential influence on physical performance. Studies have shown that the 577R genotype of ACTN3 is more prevalent in sprint athletes, while the 577X genotype is more prevalent in endurance athletes. In swimming, both power and endurance related phenotypes are equally needed for swimmers to excel at the elite level. Therefore, the ACTN3 R577X polymorphism may become a genetic marker for swimmers. The study aimed to examine the association of the ACTN3 R577X genotype with the performance of elite middle-long distance (MLD) swimmers. The distributions of the ACTN3 R577X (rs1815739) genotype and allele were examined in a general population (206) and a group of elite MLD swimmers (160) in China by using PCR-RFLP and TOF. Compared with the general population, the elite MLD swimmers, especially the females, had a higher frequency of the RR genotype. The swimmers had a higher frequency of the R allele than the general population. However, the difference was not statistically significant. After being stratified by performance, the difference of the R allele frequency between the international master athletes and the general population was statistically significant. The elite MLD swimmers had a higher frequency of the RR genotype than the RX+XX genotype compared with the general population. The ACTN3 R577X polymorphism was associated with the performance of elite MLD swimmers in China. The SNP R577X could be used as a biomarker for selecting elite MLD swimmers in China.